Sources of agricultural growth in India: role of diversification towards high-value crops - Joshi, Pramod Kumar; Birthal, Pratap Singh; Minot, Nicholas (International Food Policy Research Institute, 2006)
This study examines the sources of crop income growth in Indian agriculture over the 1980s and 1990s. Using a method developed by Minot (2003), the analysis decomposes crop income growth into the contribution of yield increases, area expansion, price increases, and diversification from low-value crops to higher-value crops. The results confirm that at the national level, technology (higher yield) was the main source of crop income growth during 1980s, while rising prices and diversification emerged as the dominant sources of growth in agriculture during 1990s. Diversification towards higher-value crops such as fruits and vegetables accounted for about 27% of crop income growth in the 1980s and 31% in the 1990s. However, these national averages hide substantial regional variation. In the grain-dominated northern and eastern regions, price increases were the most important source of growth during 1990s, while in the southern and western regions crop income growth was led by diversification into higher-value crops. The results reflect the slowing growth of wheat and rice yields in India, as well as the growing importance of diversification into higher-value crops. Restoring the growth in grain yields will require investment in agricultural research and development, while facilitating further diversification involves institutional development to better link small farmers with growing markets for high-value commodities.